First documented record of the Reddish back thrush, Catharus fuscescens (Aves : Turdidae) in Loreto, Peru - Fong Rengifo, Esteban Eduardo (2020)
On October 5, 2019, an individual from Catharus fuscescens was captured, as part of the monthly sampling of the project Monitoring of birdlife populations in the department of Loreto - Peru conducted by the Loreto Bird Observatory - LBO in the San Rafael community, Indiana district, department of Loreto. This capture represents the first documentation of C. fuscescens for the department of Loreto, confirming the suggested condition of a rare migrant in the northeastern end of Peru as it moves south as its migration season to South America.